1321+045: A compact steep‐spectrum radio source in a cool‐core galaxy cluster. Issue 9 (20th October 2021) - O'Sullivan, Ewan; Kunert‐Bajraszewska, Magdalena; Siemiginowska, Aneta; Burke, Douglas J.; Combes, Françoise; Salomé, Philippe; Giacintucci, Simona
Abstract: Cluster‐central gigahertz peak and compact steep‐spectrum (CSS) sources offer an opportunity to study the earliest phases of active galactic nucleus (AGN) feedback, but few have yet been examined in detail. We present results from radio and X‐ray observations of 1321+045, a CSS source in a 4.4 keV cluster at z = 0.263 . The cluster has a strongly cooling core, and disturbances from a minor cluster merger may have triggered a period of jet activity which formed the 16 kpc radio lobes 2.0 − 0.2 + 0.3 Myr ago. However, new very long baseline array (VLBA) imaging shows a ∼20 pc jet on a different projected axis, which is probably only a few hundred years old. We consider possible histories for the system, with either one or two periods of jet activity. While this single system is informative, a broader study of the youngest cluster‐central radio sources is desirable.